Foreign Minors in Poland: Legal and Educational Aspects - Bogdan Stańkowski (Ignatianum University Press, 2023)
The author takes up the problem of foreign minors living in Poland, which was first noticed in this country at the beginning of the 1990s. In the Polish literature on the subject, the problem of migration and minors is most often discussed in the context of labour migration of Poles and problems related to the absence of parents in Poland. The problem of foreign minors living in Poland fits into a wider European context. The objective of this article is to understand the legal and demographic aspects of foreign minors as well as the dilemmas and challenges faced by Polish schools in the area of education. To pursue this cognitive objective, the author conducted an analysis of the relevant literature. In order to investigate the topic, two research questions were formulated: a) What is the Polish migration policy towards foreign minors from the legal perspective? b) What is the situation of foreign minors in Polish schools, including legal norms and problems connected with their education and upbringing? In conclusion, it should be stated that Poland lacks a broad strategy and holistic policy from the government and non-governmental institutions on the integration of foreigners. Nevertheless, Polish law and institutional practices are aimed at safeguarding the interests of foreign minors and respecting children's rights, their subjectivity, and national and cultural identity. The upbringing of minor foreigners living in Poland poses new challenges for schools and teachers, who should acquire new competences in intercultural education and educational practices aimed at students from other cultures. It should also be noted that there are no specialised centres capable of providing adequate care and assistance to such children, who are often victims of violence, crime and exploitation. Educational authorities and schools tend to incline towards the paradigm of inclusion and acknowledging the 'Other' when it comes to children from other cultures, rather than discrimination and opposition to the process of multiculturalism.